Maternally Transferred Antibodies from DNA-Immunized Avians Protect Offspring against Hepadnavirus Infection - Rollier, Christine (American Society for Microbiology, 2000)
The outcome and protective efficacy of maternal antibodies elicited by DNA immunization to the large (L) hepadnavirus envelope protein were studied using the duck hepatitis B virus (DHBV) model. Following genetic immunization of breeding ducks with a DHBV L protein gene-bearing plasmid, specific and highly neutralizing antibodies were transferred from the sera of immunized ducks, via the egg yolk, to the progeny of vaccinees. Interestingly, large amounts (60 to 100 mg/egg) of high-titer and L protein-specific yolk immunoglobulins (immunoglobulin Y) accumulated in the egg yolk. These results suggest that eggs from genetically immunized avians may represent a potent source of DNA-designed antibodies specific to viral antigen. Importantly, these antibodies are vertically transmitted and protect offspring against high-titer DHBV challenge.